AB0191 Prevalence of osteoporosis among female systemic lupus erythematosus patients. (1st June 2001) - Di Munno, O; Mazzantini, M; Mosca, M; Frigelli, S; Sedie, A Delle; Neri, R; Bombardieri, S
Abstract : Background: It has been reported that bone mineral density (BMD) is significantly reduced in premenopausal SLE patients as compared to controls and that 12–25% of such patients are considered to have osteoporosis (OP). Furthermore, SLE patients have a 5-fold probability of sustaining a fracture as compared to the normal population. Long term glucocorticoids (GC) and immunosoppressive drugs are likely to play a major role in the pathogenesis of bone loss. Objectives: Aim of the present study was to assess BMD and OP prevalence among ambulatory female SLE patients with respect to a normal population. Methods: Thirty-two pre- (mean age 36 ± 9 years) and 14 postmenopausal (mean age 57 ± 8) patients have been enrolled so far. Exclusion criteria were: any other disease known to affect bone mass, renal insufficiency (serum cretinine > 2 mg/dl for > 6 months), any treatment for > 1 month for the prevention and treatment of bone loss, excluded calcium and vitamin D supplementation. Lumbar and femoral BMD were measured by dual x-ray absorptiometry (DXA). All patients were receiving GC at the time of the study. Variables included were: body mass index, disease duration, activity (ECLAM) and damage (SLICC), duration of GC treatment, cumulative dose of GC (either by pulse therapy and daily oral dose), and use of the immunosoppressive agent cyclophosphamide. Results: In premenopausal patients mean lumbar BMD was 0.96 ± 0.13 g/cm 2 (mean T-score -0.8 ± 1.2), and femoral BMD was 0.87 ± 0.19 g/cm 2 (T-score – 0.8 ± 1.1); in postmenopausal patients lumbar BMD was 0.85 ± 0.13 g/cm 2 (T-score -1.8 ± 1.2) and femoral BMD 0.84 ± 0.11 (T-score -1.2 ± 0.9). OP, defined as a T-score below 2.5 SD compared to a reference population of young healthy women in at least one region of measurement, was detected in 4 (12.5%) premenopausal and in 3 (21.4%) postmenopausal patients. Comparison to the normal population and the correlations between BMD and the variables included will be evaluated only after the completion of the recruitment. Conclusion: These preliminary results show in our SLE patients a prevalence of OP which is similar to that reported in other series. The role of the variables included in the analysis will help understand the pathogenesis of bone loss.